Increased Peatland Nutrient Availability Following the Fort McMurray Horse River Wildfire - Christine van Beest; Richard Petrone; Felix Nwaishi; James Michael Waddington; Merrin Macrae (Diversity, 2019)
Northern peatlands are experiencing increased wildfire disturbance, threatening peatland biogeochemical function and ability to remain major stores of carbon (C) and macronutrients (nitrogen—N, and phosphorus—P). The impacts of climate change-driven drying on peatland nutrient dynamics have been explored previously; however, the impacts of wildfire on nutrient dynamics have not been examined when comparing burned and unburned areas in a post-fire fen. This study assessed the impact of wildfire on N and P bioavailability, change in CNP stoichiometric balance and feedback on plant nutrient limitation patterns in a fen peatland, one-year post-wildfire, by comparing Burned and Unburned areas. Water extractable P increased up to 200 times in shallow leachate, 125 times in groundwater and 5 times in peat. Surface ash leachate had increased concentrations in Ammonium (NH4+) and Nitrate (NO3−), and through groundwater mobility, increased extractable N concentrations were observed in peat throughout the entire fen. The net mineralization of N and P were minimal at the Burned areas relative to Unburned areas. Fire affected plant nutrient limitation patterns, switching from dominantly N-limited to NP co-limited and P-limitation in moss and vascular species respectively. The top 20 cm of the Burned area C concentrations was higher relative to the Unburned area, with increased CN and CP ratios also being found in the Burned area. These findings suggest that the long-term effects of elevated C, N, and P concentrations on plant productivity and decomposition must be re-evaluated for fire disturbance to understand the resiliency of peatland biogeochemistry post-wildfire.